Colored silicon polymer material and preparation method thereof
By using specific silicon monomer synergistic and conjugated systems in soft contact lens materials, the problems of insufficient high water content, low oxygen permeability and anti-inflammatory properties of existing materials are solved, and low water content, high oxygen permeability, softness and toughness are achieved, and anti-inflammatory properties are significantly improved.
Patent Information
- Application Number
- CN202411808624.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
Existing soft contact lens materials have the risk of high moisture content leading to worsening of dry eyes, low oxygen permeability, difficulty in taking into account both softness and toughness, and prone to tears contamination and bacterial reproduction.
By selecting suitable silicon monomers for synergistic action, a silicon polymer material with low water content, high oxygen permeability and moderate toughness is prepared, suitable for use in ophthalmic lenses, and a specific proportion of three monomers and dyes are added to the material to form a conjugated system to improve anti-inflammatory performance.
The combination of low water content, high oxygen permeability, softness and toughness is achieved, reducing the risk of tear adsorption and bacterial reproduction, and significantly improving anti-inflammatory properties and reducing the risk of corneal edema and dry eyes.
Smart Images

Figure BDA0005179956370000041 
Figure BDA0005179956370000051 
Figure BDA0005179956370000061
Abstract
Description
Technical Field
[0001] The present invention relates to medical devices made of silicon polymer materials, such as colored medical devices and preparation methods thereof. Furthermore, contact lenses made of the silicon polymer materials of the present invention have properties such as high oxygen permeability, low water content, softness, and anti-inflammatory properties. Background Art
[0002] Corneal oxygen metabolism is a key link in the eye's sugar metabolism, energy metabolism, electrolyte metabolism, and water balance metabolism. The cornea is crucial for oxygen intake. The oxygen required for corneal glucose metabolism is mainly provided by the tear film. When the eyes are open, the tear film is in direct contact with the atmosphere, and the oxygen in the atmosphere is directly provided to the cornea through the tear film. When wearing contact lenses, the channel for direct oxygen supply between the cornea and the outside world is blocked. Therefore, the contact lens material must have sufficient oxygen permeability to meet the corneal oxygen metabolism function and ensure the wearer's corneal safety. Contact lenses can be divided into hydrogel contact lenses and non-hydrogel contact lenses according to the water content of the lens material. Hydrogel contact lenses are generally soft contact lenses, which have a water content of ≥10% after equilibrium in a standard saline solution, including hydrogel contact lenses and silicone hydrogel contact lenses. Non-hydrogel contact lenses are currently mainly hard contact lenses with a water content of less than 10% (such as RGP lenses / scleral lenses / orthokeratology lenses, etc.), but soft low-water-content, high-oxygen-permeability contact lenses are rarely available.
[0003] Currently available soft contact lenses are generally hydrogel (silicon-containing hydrogel) contact lenses with a water content of 25% to 80%. Some wearers experience a stronger sense of dryness and discomfort than naked eyes, and even worse dry eye symptoms. This may be caused by the lens absorbing water from tears and increasing tear evaporation after wearing the lens. In addition, due to its high water content, it is difficult for hydrogel contact lenses to achieve a high oxygen permeability and cannot meet the requirements of long-term continuous wear; silicone hydrogel contact lenses increase the oxygen permeability of the lens by adding silicon-containing components to the lens material. Due to the need to consider the compatibility of lipophilic silicone components and hydrophilic components, it is difficult to take into account the oxygen permeability and softness and comfort of silicone hydrogel lenses. In addition, hydrogel (silicon-containing hydrogel) material water-containing contact lenses are easily contaminated by tear components, and because the material contains a large amount of water, there is also a risk of bacterial growth. The base material of non-hydrogel contact lens materials contains almost no hydrophilic components, is not restricted by the compatibility of hydrophobic silicone monomers and hydrophilic monomers, has good material transparency, excellent lens optical properties, and higher visual clarity. Since the proportion of silicon monomers in the material is not limited, the oxygen permeability coefficient of the lens can be as high as 300 or more, ensuring the safety of long-term continuous wear. Existing non-hydrogel contact lenses are generally hard contact lenses made of hard fluorosilicone acrylate. Although they have the advantages of low water content and high oxygen permeability, the hardness of the lens substrate reduces wearing comfort and may cause corneal injury when the fitting parameters are not matched or the lens is damaged. Non-hydrogel soft contact lenses are mainly made of traditional silicone rubber and have gradually faded out of the market. The main reasons are: (1) The silicone monomer composition of traditional silicone rubber is simple and cannot have mechanical properties such as high oxygen permeability, softness and toughness; (2) Traditional silicone rubber soft contact lenses cannot be widely used due to the high surface viscosity, which makes it very easy to adhere to the cornea (fixation) or the silicone rubber substrate material cannot be firmly combined with the hydrophilic coating.
[0004] The art hopes to obtain a material with low oxygen permeability, flexibility and strength, and suitable for surface coating. The inventors of the present invention utilize the advantages of high oxygen permeability and low water content of non-hydrogels to solve the problems of the prior art and provide a silicone polymer material with low water content, high oxygen permeability, moderate toughness, and suitable for hydrophilic coating, which is particularly suitable for use in ophthalmic lenses and has unexpected resistance to protein and lipid adsorption, and is particularly suitable for use in the preparation of low-water soft contact lenses for correcting human eye refractive errors.
[0005] The environment, microorganisms, hormone imbalance and genetics can all stimulate inflammation of the ocular surface. For example, dry eye can cause eye discomfort, limit reading, driving and recreational activities, and greatly affect the quality of life related to vision. Therefore, the art also hopes to further develop materials with therapeutic functions without affecting basic needs, such as materials with anti-inflammatory properties, for example, suitable for people with more common eye diseases, such as ophthalmic inflammation.
[0006] In addition, there is a need in the art for low-water materials that can correct refractive errors of the human eye, especially integrally colored materials, such as those suitable for soft contact lenses, which not only have color, but also have anti-inflammatory, low-water content, moderate toughness and colored silicone polymer materials suitable for hydrophilic coatings. Summary of the invention
[0007] The present invention solves the problems of water evaporation, dry eye, bacterial growth, protein and lipid adsorption in soft contact lenses containing silicone hydrogel (generally referred to as hydrogel) in the prior art, and provides a contact lens material that has low water content and high oxygen permeability, excellent mechanical properties such as softness and toughness, and is suitable for surface coating, as well as a contact lens prepared from the same.
[0008] The inventors unexpectedly discovered that the silicon polymer material of the present invention solves the problems existing in the above-mentioned prior art. The silicon polymer material is prepared by the synergistic effect between the silicon monomers selected by the present invention. The obtained silicon polymer material of the present invention can take into account low water content, high oxygen permeability, softness and improved mechanical properties such as toughness, and has unexpected resistance to protein and lipid adsorption.
[0009] In particular, the inventors unexpectedly discovered that the silicone polymer material of the present invention has improved anti-inflammatory properties of the material. Without wishing to be bound by theory, the inventors believe that the silicone polymer material of the present invention contains three monomers in a specific ratio and a third monomer, a styrene-based silicon monomer, in a specific content, and dyes and / or pigments such as anthocyanins, anthocyanins and other molecules can form a conjugated system in the polymer matrix of the specific ratio of monomers formed in the present invention, so that the silicone polymer material of the present invention (and the contact lenses prepared therefrom) has significantly improved anti-inflammatory properties on the basis of good comfort, and can reduce the risk of corneal edema and dry eyes during long-term wear.
[0010] The silicon polymer material of the present invention is a silicon polymer material prepared by polymerization through the synergistic effect of the following silicon monomers, wherein:
[0011] The first silicon monomer is selected from acrylate or acrylamide short-chain aliphatic silicon monomers;
[0012] The second silicon monomer is selected from a single-terminated or double-terminated long-chain polysiloxane monomer of acryloxy or acrylamide type;
[0013] The third silicon monomer is selected from styrene-based aromatic silicon monomers.
[0014] The present invention also relates to medical devices comprising the silicone polymer material of the present invention, such as contact lenses, color-developing contact lenses, colored contact lenses, intraocular lenses, artificial corneas, intracorneal rings, intracorneal lenses, intraocular fillings, etc., in particular, low-water-content soft contact lenses, which may or may not be equipped with electronic devices.
[0015] The present invention also relates to a method for preparing a silicon polymer material, comprising:
[0016] -(1) mixing the required components, such as a first silicon monomer, a second silicon monomer, a third silicon monomer, a crosslinking agent, an initiator or a dye and / or a pigment, a light absorber, and optionally removing bubbles;
[0017] - (2) polymerizing the mixture, optionally placing it in a mold for polymerization, preferably by thermal polymerization and / or photopolymerization; then, optionally, subjecting the obtained polymer to subsequent treatment such as molding.
[0018] Silicon Monomer
[0019] In the present invention, the first silicon monomer (Si1) and the second silicon monomer (Si2) have similar acrylate and / or acrylamide structures. By controlling the usage ratio of the two, the first silicon monomer plays a solubilizing role on the second silicon monomer, thereby increasing the proportion of the second silicon monomer, i.e., the long-chain polysiloxane monomer, in the polymer material, which is beneficial to improving the flexibility of the medical device material without affecting the optical transparency of the material; the third silicon monomer (Si3) is a styrene-based aromatic silicon monomer, which has a relatively high free volume, and the rigid styrene conjugated structure is beneficial to improving the mechanical strength of the material. Through its synergistic effect with the second silicon monomer, the long-chain polysiloxane is filled in the gaps of the third silicon monomer, making the material denser and increasing the content of silicon atoms that transmit oxygen, thereby improving the mechanical strength of the material such as toughness and also improving the oxygen permeability of the material.
[0020] The synergistic relationship between the three silicon monomers, such as Figure 1 As shown, Figure 1 For example, Figure 1 The ratio between silicon monomers is not strictly shown.
[0021] As described in the present invention, the synergistic effect of the three silicon monomers makes the silicon polymer material described in the present invention a silicon polymer material with low water content, high oxygen permeability, moderate toughness and suitability for hydrophilic coating, which is particularly suitable for use as a material for ophthalmic lenses and has unexpected resistance to protein and lipid adsorption, and is particularly suitable for the preparation of low-water soft contact lenses for correcting refractive errors of the human eye.
[0022] The first silicon monomer is a short-chain aliphatic silicon monomer. According to a specific embodiment of the present invention, the first silicon monomer is specifically selected from at least one of acrylate or acrylamide silicon monomers, for example, the molecular structure is:
[0023]
[0024] in:
[0025] R1=H or C 1-6Alkyl, preferably H or CH3;
[0026] n=1-20, preferably 1-6, especially 2-5, even 3 or 4;
[0027] R2, R3 and R4, which may be the same or different, are selected from H, CH3, OCH3, OCH2CH3, OSi(CH3)3, CH(OCH2CH3)2 and C(OCH2CH3)3.
[0028] According to a specific embodiment of the present invention, the first silicon monomer can be selected from: 3-(trimethoxysilyl)propyl acrylate, 3-(trimethoxysilyl)propyl methacrylate, 3-[dimethoxy(methyl)silyl]propyl methacrylate, 3-[diethoxy(methyl)silyl]propyl methacrylate, 3-(methoxydimethylsilyl)propyl acrylate, 3-(triethoxysilyl)propyl methacrylate, 3-[tri(trimethylsiloxy)silyl]propyl methacrylate, acrylamidopropyl trimethoxysilane, (3-methacrylamidopropyl)triethoxysilane, 3-acrylamidopropyl tri(trimethylsiloxy)silane, (3-methacrylamidopropyl)tri(trimethylsiloxy)silane, and the like.
[0029] The second silicon monomer is a long-chain polysiloxane monomer, and according to a specific embodiment of the present invention, it is preferably one or more of polydimethylsiloxanes with single or double end capping of acryloyloxy or methacryloyloxy or acrylamide or methacrylamide, and its molecular weight is above 1000, preferably 1500 to 50000, more preferably 1500 to 20000, or 3000 to 15000, or even 5000 to 10000. For example, the molecular structure is:
[0030]
[0031] in:
[0032] W is X-(CH2)pY(CH2)q;
[0033] R'1=H or C 1-6 Alkyl, preferably H or CH3;
[0034] p=1-20, preferably 1-6, especially 2-5, even 3 or 4;
[0035] q=1-20, preferably 1-6, especially 2-5, even 3 or 4;
[0036] m=1-100, preferably 15-60, especially 20-40;
[0037] X is selected from O, S or NH;
[0038] Y is absent or selected from O or S or NH or NHCOO(CH2)tO or NHCOO(CH2)tS or NHCOO(CH2)tNH, where t=1-20, preferably 1-6, especially 2-5, even 3 or 4;
[0039] R'2 and R'3, the same or different, are selected from H or linear or branched, saturated or unsaturated C 1-20 Alkyl; or C 6-20 Arylalkyl, either straight chain or C 6-20 One or more of heteroarylalkyl or OCH3 or OCH2CH3 or OSi(CH3)3 or CH(OCH2CH3)2 or C(OCH2CH3)3;
[0040] R'4 is selected from H or linear or branched, saturated or unsaturated C 1-20 Alkyl or C 6-20 Arylalkyl, either straight chain or C 6-20 Heteroarylalkyl; preferably C1-4 alkyl.
[0041] The third silicon monomer is an aromatic silicon monomer. According to a specific embodiment of the present invention, it is preferably selected from a styrene-containing silicon monomer, for example, the molecular structure is:
[0042]
[0043] R"1 = H or C1-6 alkyl, preferably H or CH3;
[0044] R"5 and R"6 are selected from H or linear or branched, saturated or unsaturated C 1-20 Alkyl, or one or more of Si(CH3)3;
[0045] X' is absent or O or S or linear or branched, saturated or unsaturated C 1-20 Alkyl; or C 6-20 Arylalkyl, or C 6-20 heteroarylalkyl; or C 3-20 heterocyclylalkyl;
[0046] R"2, R"3 and R"4 are the same or different and are selected from one or more of CH3, OSi(CH3)3, OSiCH2CH2Si(CH3)3 and SiCH2CH2Si(CH3)3.
[0047] In addition to the structures listed in the above formula, the aromatic silicon monomers in the present invention may also include silicon monomers containing an "aryl" group in the structure, wherein the "aryl" group may refer to a phenyl group (i.e., a monocyclic aromatic group) or a bicyclic system containing at least one benzene ring or an aromatic bicyclic ring containing only carbon atoms in the aromatic bicyclic system. The bicyclic aromatic group may be selected from azulenyl, naphthyl, or a phenyl group fused to a monocyclic cycloalkyl, a monocyclic cycloalkenyl, or a monocyclic heterocyclic group, wherein in particular, the bicyclic aromatic group is connected to the parent molecular part through any carbon atom contained in the phenyl part of the bicyclic system or any carbon atom of the naphthyl or azulenyl ring, wherein in particular, the fused monocyclic cycloalkyl or monocyclic heterocyclic group part of the bicyclic aromatic group is optionally substituted with one or two oxo and / or thia groups. Representative examples of bicyclic aryl groups include, but are not limited to, azulenyl, naphthyl, indan-1-yl, indan-2-yl, indan-3-yl, indan-4-yl, 2,3-dihydroindol-4-yl, and the like.
[0048] In the present invention, the weight ratio of the first silicon monomer: the second silicon monomer: the third silicon monomer is (40-55): (40-60): (0.1-5), or even (40-50): (45-59): (0.2-4), in particular (40-48): (50-58): (0.3-3), and preferably (40-45): (52-58): (0.5-2.5).
[0049] Crosslinking agent
[0050] In the present invention, according to a specific embodiment of the present invention, the crosslinking agent can be selected from one or more of ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tri(ethylene glycol) divinyl ether, tetraethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, trimethylolpropane trimethacrylate, glycerol dimethacrylate, glycerol trimethacrylate, propylene glycol dimethacrylate, 1-(acryloyloxy)-3-(methacryloyloxy)-2-propanol, polyethylene glycol dimethacrylate (wherein the polyethylene glycol preferably has a molecular weight of up to about 5000), vinyl methacrylate, ethylenediamine dimethylacrylamide, and triallyl isocyanurate.
[0051] According to one embodiment of the present invention, the amount of the crosslinking agent is 0.02 to 5%, or 0.05 to 4%, in particular 0.1 to 3%, or even 0.15 to 1%, based on the total mass (100%) of the components of the present invention.
[0052] Pigments and / or dyes
[0053] In silicon polymer material of the present invention, pigment and / or dyestuff can be added to enable material to obtain different colors, it is selected from but not limited to the compound that can be used for contact lenses of U.S. FDA approval. Specifically, can be selected from synthetic pigment and / or dyestuff or natural pigment and / or dyestuff, for example copper phthalocyanine, reactive blue 4, reactive blue 19, reactive blue 21, reactive blue 246, reactive blue 247, reactive yellow 15, reactive orange 78, reactive red 11, titanium dioxide, reactive black 5, D&C green 4, D&C blue 6, D&C green 6, D&C yellow 10, fluorescein sodium, brilliant blue, eosin, carmine, lemon yellow, amaranth, erythrosine, new red, indigo, acid red, lycopene. Especially, can use the yellow dye compound that contains azo group in the molecular structural formula.
[0054] According to one embodiment of the present invention, pigment and / or dye compounds containing polymerizable groups can be used, wherein the polymerizable groups can be selected from vinyl, allyl, butenyl, ethynyl, acryloxy, methacryloyloxy, acrylamide, methacrylamide, vinyl ether.
[0055] According to a specific embodiment of the present invention, the natural pigment and / or dye comprises a natural pigment, for example, selected from anthocyanins, anthocyanidins, wolfberry pigments, grape skin pigments, gardenia blue pigments, red rice red pigments, adzuki bean red pigments, and betalain red pigments.
[0056] According to a specific embodiment of the present invention, the content of the synthetic pigment and / or dye, or natural pigment and / or dye is 0.001 to 10% by mass, or 0.01 to 6%, in particular 0.1 to 4%, or even 0.2 to 2%.
[0057] Additives
[0058] In the process of preparing the silicon polymer material of the present invention, an initiator may be used, and a photoinitiator or a thermal initiator may be used. The photoinitiator may be selected from, but not limited to, benzoin methyl ether, diethoxyacetophenone, benzoylphosphine oxide initiator, dimethylaminobenzoic acid ethyl ester, 2-isopropylthioxanthone, 1-hydroxycyclohexyl phenyl ketone, Darocure series initiator or Irgacure series initiator. Among them, the initiator is preferably Irgacure-819, or Darocure-1173. The thermal initiator includes, but is not limited to, azo or peroxide initiators, such as azobisisoheptanenitrile (ADVN), azobisisobutyronitrile (AIBN), benzoyl peroxide (BPO), Trigonox series initiator or Perkdox series initiator.
[0059] According to one embodiment of the present invention, the amount of the initiator is 0.02 to 5%, or 0.05 to 4%, in particular 0.1 to 3%, or even 0.2 to 2%, based on the total mass (100%) of the components of the present invention.
[0060] Ultraviolet light absorbers, blue light absorbers, etc. may be added to the silicon polymer material of the present invention.
[0061] The ultraviolet light absorber includes but is not limited to: a compound selected from the group having an efficient absorption function for ultraviolet light with a wavelength range below 380 nm. Preferably, the benzophenone compounds and / or benzotriazole compounds are highly safe. More preferably, the benzophenone compounds and / or benzotriazole compounds contain a polymerizable group, and the polymerizable group is selected from the group consisting of vinyl, allyl, butenyl, ethynyl, acryloyloxy, methacryloyloxy, acrylamide, methacrylamide, and vinyl ether.
[0062] The blue light absorber includes but is not limited to: a compound selected from the group having a selective filtering function for blue light within a wavelength range of 400 to 500 nm. A yellow dye compound containing an azo group in the molecular structure is preferred. A yellow dye compound containing a polymerizable group is more preferred, and the polymerizable group is selected from the group consisting of vinyl, allyl, butenyl, ethynyl, acryloyloxy, methacryloyloxy, acrylamide, methacrylamide, and vinyl ether.
[0063] According to a specific embodiment of the present invention, based on the total mass (100%) of the components of the present invention, the amount of ultraviolet absorber and blue light absorber is 0 to 3%, or 0.01 to 2%, especially 0.02 to 1%, or even 0.05 to 0.5%.
[0064] In the process of preparing the silicon polymer material of the present invention, a diluent such as a solvent and / or a hydrophilic polymer may also be added. When the material contains a diluent, the reactive components are usually mixed in the diluent to form a reaction mixture. Applicable diluents may include alcohols having 2 to 20 carbon atoms, carboxylic acids having 8 to 20 carbon atoms, poly-N,N-dimethylacrylamide, polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, amides derived from primary amines having 10 to 20 carbon atoms and carboxylic acids having 8 to 20 carbon atoms, and the like. Specifically, the diluent may include one or more of 1-ethoxy-2-propanol, diisopropylaminoethanol, isopropanol, 3,7-dimethyl-3-octanol, 1-decanol, 1-dodecanol, 1-octanol, 1-pentanol, 2-pentanol, 1-hexanol, 2-hexanol, 2-octanol, 3-methyl-3-pentanol, tert-pentanol, tert-butanol, 2-butanol, 1-butanol, 2-methyl-2-pentanol, 2-propanol, 1-propanol, ethanol, 2-ethyl-1-butanol, 1-tert-butoxy-2-propanol, 3,3-dimethyl-2-butanol, tert-butoxyethanol, 2-octyl-1-dodecanol, decanoic acid, octanoic acid, dodecanoic acid, 2-(diisopropylamino)ethanol, poly N,N-dimethylacrylamide, polyvinyl alcohol, polyethylene glycol, and polyvinyl pyrrolidone.
[0065] According to one embodiment of the present invention, the amount of the diluent is 0 to 15%, or 0.5 to 12%, in particular 1 to 10%, or even 2 to 8%, based on the total mass (100%) of the components of the present invention.
[0066] The present invention also relates to a method for preparing the silicon polymer material of the present invention, comprising the following steps:
[0067] -(1) mixing the required components, such as a first silicon monomer, a second silicon monomer, a third silicon monomer, a dye and / or a pigment, a crosslinking agent, and optionally an initiator or a light absorber, and optionally removing bubbles;
[0068] - (2) polymerizing the mixture, optionally placing it in a mold for polymerization, preferably by thermal polymerization and / or photopolymerization; then, optionally, subjecting the obtained polymer to subsequent treatment such as molding.
[0069] The present invention also relates to a method for preparing a medical device such as a contact lens obtained from the silicon polymer material of the present invention, comprising the following steps:
[0070] -(1) mixing the required components, such as a first silicon monomer, a second silicon monomer, a third silicon monomer, a dye and / or a pigment, a crosslinking agent, and optionally an initiator or a light absorber, and optionally removing bubbles;
[0071] - (2) polymerizing the mixture, optionally placing it into a mold such as a mold for a medical device (e.g., a contact lens), preferably by thermal polymerization and / or photopolymerization;
[0072] -(3) optionally, extracting with an organic solvent;
[0073] - (4) optionally, a hydration step, an equilibration step with a balanced saline solution, and a sterilization step;
[0074] -(5) Molding to prepare a substrate.
[0075] According to a specific embodiment of the present invention, the step of surface grafting a hydrophilic polymer is also included, including: immersing the substrate of the medical device (such as a contact lens) in a solution containing the hydrophilic polymer and an oxidant, and then performing a chemical reaction to obtain the medical device. Since the first silicon monomer and the second silicon monomer in the silicon polymer material of the present invention contain acrylate and acrylamide structures, the hydrophilic polymer is easier to spread on the surface of the lens substrate, and then covalently grafted on the surface under the action of the oxidant to form a uniform and stable hydrophilic coating. Preferably, the hydrophilic polymer is selected from one or more of the following: a hydrophilic polymer containing a cyclic amide or cyclic imine structure in the main chain, poly N,N-dimethylacrylamide, polyvinyl alcohol, polyethylene glycol, polyacrylic acid, polyethylene oxide, poly 2-ethyl-oxazoline, a polymer containing a phosphorylcholine vinyl monomer, and one or more polysaccharides, preferably polyvinyl pyrrolidone, poly N-vinyl-2-piperidone, poly N-vinyl-2-caprolactam, poly N-vinyl-3-methyl-2-caprolactam, poly N-vinyl-3-methyl-2-piperidone, poly N-vinyl-4-methyl-2-piperidone, poly N-vinyl-4-methyl-2-caprolactam, poly N-vinyl-3-ethyl-2-pyrrolidone, poly N-vinyl-4,5-dimethyl-2-pyrrolidone, and polyvinyl imidazole.
[0076] According to a specific embodiment of the present invention, the oxidant can be selected from one or more of peroxides or persulfides, preferably one or more of hydrogen peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate.
[0077] The present invention also relates to a medical device, preferably, a contact lens, a color contact lens, a colored contact lens, an intraocular lens, an intraocular lens, an artificial cornea, an intracorneal ring, an intracorneal lens, a drug release carrier, an intraocular filler, a medical device lens or a medical treatment device such as a device for treating ophthalmic diseases, preferably a soft contact lens with low water content, which may or may not be equipped with electronic devices. Contact lenses equipped with electronic devices such as sensors are based on measuring changes in resistance, inductance and capacitance generated in response to pressure-induced strain. Electronic sensing methods are sensitive to the hydration level of contact lenses. Therefore, electronic sensors for contact lenses are generally made of silicone rubber (which has a very low water content).
[0078] Specifically, the present invention relates to the following embodiments:
[0079] Item 1. A silicon polymer material, which is polymerized from silicon monomers and contains dyes and / or pigments, wherein the silicon monomers include at least a first silicon monomer, a second silicon monomer, and a third silicon monomer,
[0080] The first silicon monomer is selected from short-chain aliphatic silicon monomers, the second silicon monomer is selected from long-chain polysiloxane monomers, and the third silicon monomer is selected from aromatic silicon monomers.
[0081] The weight ratio of the first silicon monomer: the second silicon monomer: the third silicon monomer is (30-70): (20-60): (0.05-10).
[0082] Item 2. The silicon polymer material according to Item 1, wherein the first silicon monomer is selected from at least one of acrylate or acrylamide silicon monomers, such as a short-chain aliphatic silicon monomer of the following formula:
[0083]
[0084]
[0085] R1=H or C 1-6 Alkyl, preferably H or CH3;
[0086] n = 1-20, preferably 1-6, even 2-5;
[0087] R2, R3 and R4 may be the same or different and are selected from one or more of H, CH3, OCH3, OCH2CH3, OSi(CH3)3, CH(OCH2CH3)2 and C(OCH2CH3)3.
[0088] Item 3. A silicon polymer material according to any of the preceding items, wherein the first silicon monomer is selected from: 3-(trimethoxysilyl)propyl acrylate, 3-(trimethoxysilyl)propyl methacrylate, 3-[dimethoxy(methyl)silyl]propyl methacrylate, 3-[diethoxy(methyl)silyl]propyl methacrylate, 3-(methoxydimethylsilyl)propyl acrylate, 3-(triethoxysilyl)propyl methacrylate, 3-[tri(trimethylsiloxy)silyl]propyl methacrylate, acrylamidopropyltrimethoxysilane, (3-methacrylamidopropyl)triethoxysilane, 3-acrylamidopropyltri(trimethylsiloxy)silane, (3-methacrylamidopropyl)tri(trimethylsiloxy)silane.
[0089] Item 4. A silicon polymer material according to any one of the preceding items, wherein the second silicon monomer is selected from one or more of acryloxy or methacryloxy or acrylamide or methacrylamide mono-terminated or di-terminated polydimethylsiloxanes, such as a long-chain polysiloxane monomer of the following formula:
[0090]
[0091] R'1=H or C 1-6 Alkyl, preferably H or CH3;
[0092] p = 1-20, preferably 1-6, or even 2-5;
[0093] q = 1-20, preferably 1-6, or even 2-5;
[0094] m=1-100, preferably 15-60;
[0095] X is O, S or NH;
[0096] Y is absent or selected from: O, S, NH, NHCOO(CH2)To, NHCOO(CH2)tS or NHCOO(CH2)tNH, where t=1-20, preferably 1-10, even 2-6, especially 3-5;
[0097] R'2 and R'3, the same or different, are selected from H or linear or branched, saturated or unsaturated C 1-20 Alkyl; or C 6-20 Arylalkyl, either straight chain or C 6-20 One or more of heteroarylalkyl or OCH3 or OCH2CH3 or OSi(CH3)3 or CH(OCH2CH3)2 or C(OCH2CH3)3;
[0098] R'4 is H or a linear or branched, saturated or unsaturated C 1-20 Alkyl or C 6-20Arylalkyl, either straight chain or C 6-20 Heteroarylalkyl; preferably C1-4 alkyl; W is X-(CH2)pY(CH2)q.
[0099] Item 5. A silicon polymer material according to any of the preceding items, wherein the second silicon monomer is selected from: bis-3-(meth)acryloxypropyl polydimethylsiloxane, α-3-(meth)acryloxypropyl-w-n-butyl-polydimethylsiloxane, bis-4-(meth)acryloxybutyl polydimethylsiloxane, α-4-(meth)acryloxybutyl-w-n-butyl-polydimethylsiloxane, bis-3-(meth)acryloxyethoxypropyl polydimethylsiloxane, α-3-(meth)acryloxyethoxypropyl-w-n-butyl-polydimethylsiloxane Oxane, bis-4-(meth)acryloxyethoxybutyl polydimethylsiloxane, α-4-(meth)acryloxyethoxybutyl-w-n-butyl-polydimethylsiloxane, bis-3-(meth)acryloxycarbamate propyl polydimethylsiloxane, α-3-(meth)acryloxycarbamate propyl-w-n-butyl-polydimethylsiloxane, bis-4-(meth)acryloxycarbamate butyl polydimethylsiloxane, α-4-(meth)acryloxycarbamate butyl-w-n-butyl-polydimethylsiloxane.
[0100] Item 6. The silicon polymer material according to any one of the preceding items, wherein the second silicon monomer has a molecular weight of greater than 1,000, preferably from 1,500 to 50,000, more preferably from 5,000 to 30,000, and especially from 8,000 to 20,000.
[0101] Item 7. The silicon polymer material according to any of the preceding items, wherein the third silicon monomer is selected from styryl-containing silicon monomers, such as styryl-containing silicon monomers of the following formula (E):
[0102]
[0103] R"1 = H or C1-6 alkyl, preferably H or CH3;
[0104] R"5 and R"6, identical or different, are selected from H or linear or branched, saturated or unsaturated C 1-20 Alkyl, or one or more of Si(CH3)3;
[0105] X' is absent or is selected from O or S or linear or branched, saturated or unsaturated C 1-20 Alkyl; or C 6-20 Arylalkyl, or C 6-20 heteroarylalkyl; or C 3-20 heterocyclylalkyl;
[0106] R"2, R"3 and R"4, which are the same or different, are selected from one or more of CH3, OSi(CH3)3, OSiCH2CH2Si(CH3)3 and SiCH2CH2Si(CH3)3.
[0107] Item 8. A silicon polymer material according to any of the preceding items, wherein the third silicon monomer is selected from: 4-[tris(trimethylsiloxy)silyl]styrene, 4-[tris(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[tris(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[tris(trimethylsiloxy)silyl]styrene, 4-[methoxybis(trimethylsiloxy)silyl]styrene, 4-[methoxybis(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[methoxybis(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[methoxybis(trimethylsiloxy)silyl]styrene, 4-[dimethoxy(trimethylsiloxy)silyl]styrene, 4-[dimethoxy(trimethylsiloxy)silyl]methylstyrene Ethylene, 3-methyl-4-[dimethoxy(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[dimethoxy(trimethylsiloxy)silyl]styrene, 4-[ethoxybis(trimethylsiloxy)silyl]styrene, 4-[ethoxybis(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[ethoxybis(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[ethoxybis(trimethylsiloxy)silyl]styrene, 4-[diethoxy(trimethylsiloxy)silyl]styrene, 4-[diethoxy(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[diethoxy(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[diethoxy(trimethylsiloxy)silyl]styrene.
[0108] Item 9. A silicon polymer material according to any of the preceding items, wherein the crosslinker is selected from one or more of ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tri(ethylene glycol) divinyl ether, tetraethylene glycol dimethacrylate, trimethylpropane trimethacrylate, trimethylolpropane trimethacrylate, glycerol dimethacrylate, glycerol trimethacrylate, propylene glycol dimethacrylate, 1-(acryloyloxy)-3-(methacryloyloxy)-2-propanol, polyethylene glycol dimethacrylate (wherein the polyethylene glycol preferably has a molecular weight of up to about 5000), vinyl methacrylate, ethylenediamine dimethylacrylamide, and triallyl isocyanurate.
[0109] Item 10. A silicon polymer material according to any of the preceding items, wherein the weight ratio of the first silicon monomer: the second silicon monomer: the third silicon monomer is (40-55):(40-60):(0.1-5), or even (40-50):(45-59):(0.2-4), in particular (40-48):(50-58):(0.3-3), and preferably (40-45):(52-58):(0.5-2.5).
[0110] Item 11. A silicon polymer material according to any of the preceding items, comprising synthetic pigments and / or dyes, or natural pigments and / or dyes, for example selected from: copper phthalocyanine, reactive blue 4, reactive blue 19, reactive blue 21, reactive blue 246, reactive blue 247, reactive yellow 15, reactive orange 78, reactive red 11, titanium dioxide, reactive black 5, D&C green 4, D&C blue 6, D&C green 6, D&C yellow 10, sodium fluorescein, brilliant blue, eosin, carmine, tartrate, amaranth, Erythrosine, new red, indigo, acid red, lycopene; in particular, the natural pigments and / or dyes contain natural pigments, for example, selected from anthocyanins, anthocyanins, wolfberry pigments, grape skin pigments, gardenia blue pigments, red rice red pigments, adzuki bean red pigments, beet red pigments; in particular, the content of the synthetic pigments and / or dyes, or natural pigments and / or dyes is 0 to 10% by mass, or 0.01 to 6%, in particular 0.2 to 4%, or even 0.5 to 2%.
[0111] Item 12. A silicone polymer material according to any of the preceding items, further comprising an auxiliary agent, such as selected from initiators, ultraviolet absorbers, blue light absorbers, dyes and diluents, in particular the initiator is selected from thermal initiators or photoinitiators, and in particular, further comprising antibacterial and lubricating components selected from polyglutamic acid, phosphorylcholine, betaine, polylysine, polyaspartic acid.
[0112] Item 13. The silicon polymer material according to any of the preceding items, having one of the following characteristics:
[0113] - moisture content <10%, preferably <3%, most preferably <1%;
[0114] - oxygen permeability>100, preferably>200, most preferably>300;
[0115] - Elastic modulus <5 MPa, preferably <3 MPa, most preferably <1 MPa.
[0116] Item 14. A contact lens made from the silicone polymer material of any one of Items 1 to 13 above.
[0117] Item 15. The contact lens according to Item 14 above, wherein the surface of the contact lens has a surface modification layer, and preferably the surface of the contact lens comprises a covalently cross-linked grafted hydrophilic polymer coating.
[0118] Item 16. A contact lens according to Item 14 or 15, wherein the hydrophilic polymer is selected from one or more of the following: a hydrophilic polymer containing a cyclic amide or cyclic imine structure in the main chain, poly N,N-dimethylacrylamide, polyvinyl alcohol, polyethylene glycol, polyacrylic acid, polyethylene oxide, poly 2-ethyl-oxazoline, a polymer containing a phosphorylcholine vinyl monomer, and one or more of a polysaccharide, preferably polyvinyl pyrrolidone, poly N-vinyl-2-piperidone, poly N-vinyl-2-caprolactam, poly N-vinyl-3-methyl-2-caprolactam, poly N-vinyl-3-methyl-2-piperidone, poly N-vinyl-4-methyl-2-piperidone, poly N-vinyl-4-methyl-2-caprolactam, poly N-vinyl-3-ethyl-2-pyrrolidone, poly N-vinyl-4,5-dimethyl-2-pyrrolidone, and polyvinyl imidazole.
[0119] Item 17. A medical device, which is made from the silicone polymer material of any one of the aforementioned items 1-13, preferably, it is a contact lens, a chromogenic contact lens, a colored contact lens, a corneal reshaping lens, a corneal contact lens, an intraocular lens, an artificial cornea, an intracorneal ring, an intracorneal lens, an intraocular filler, a medical device lens or a medical treatment device such as a device for treating ophthalmic diseases, preferably a soft contact lens, which may or may not be equipped with electronic devices.
[0120] Item 18. The medical device according to Item 17, which is a smart contact lens equipped with electronic devices that can be used for monitoring intraocular pressure and / or monitoring eye changes.
[0121] Item 19. A method for preparing a silicon polymer material according to any one of Items 1 to 13, characterized in that it comprises the following steps:
[0122] -(1) mixing the required components, such as a first silicon monomer, a second silicon monomer, a third silicon monomer, a dye and / or a pigment, a crosslinking agent, and optionally an initiator or a light absorber, and optionally removing bubbles;
[0123] (2) polymerizing the mixture, optionally placing it into a mold such as a contact lens mold for polymerization, preferably by thermal polymerization and / or photopolymerization; then, optionally, subjecting the obtained polymer to subsequent treatment such as molding treatment.
[0124] Item 20. A method for preparing a contact lens according to any one of Items 14 to 15, characterized in that it comprises the following steps:
[0125] -(1) mixing the required components, such as a first silicon monomer, a second silicon monomer, a third silicon monomer, a dye and / or a pigment, a crosslinking agent, and optionally an initiator or a light absorber, and optionally removing bubbles;
[0126] - (2) polymerizing the mixture, optionally placing it into a mold such as a contact lens mold for polymerization, preferably by thermal polymerization and / or photopolymerization;
[0127] -(3) optionally, extracting with an organic solvent;
[0128] - (4) optionally, a hydration step, an equilibration step with a balanced saline solution, and a sterilization step;
[0129] - (5) molding to prepare a substrate;
[0130] -(6) Immersing the substrate in a solution containing an oxidant and a hydrophilic polymer and covalently cross-linking and fixing the substrate.
[0131] Item 21. The method according to Item 20, wherein the oxidant is selected from: one or more of peroxides or persulfides, preferably selected from one or more of hydrogen peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate.
[0132] Item 22. A method according to Item 20 or 21, wherein the hydrophilic polymer is selected from one or more of the following: a hydrophilic polymer containing a cyclic amide or cyclic imine structure in the main chain, poly N,N-dimethylacrylamide, polyvinyl alcohol, polyethylene glycol, polyacrylic acid, polyethylene oxide, poly 2-ethyl-oxazoline, a polymer containing a phosphorylcholine vinyl monomer, and one or more of a polysaccharide, preferably polyvinyl pyrrolidone, poly N-vinyl-2-piperidone, poly N-vinyl-2-caprolactam, poly N-vinyl-3-methyl-2-caprolactam, poly N-vinyl-3-methyl-2-piperidone, poly N-vinyl-4-methyl-2-piperidone, poly N-vinyl-4-methyl-2-caprolactam, poly N-vinyl-3-ethyl-2-pyrrolidone, poly N-vinyl-4,5-dimethyl-2-pyrrolidone, and polyvinyl imidazole. BRIEF DESCRIPTION OF THE DRAWINGS
[0133] Figure 1 The synergistic relationship of the three silicon monomers of the present invention is illustrated. DETAILED DESCRIPTION
[0134] The present invention is further described below in conjunction with specific embodiments. It should be noted that those skilled in the art know that the content of the present invention is not limited by the specific embodiments.
[0135] Examples 1 to 17 Preparation of low water content soft contact lenses
[0136] The low-water-containing soft contact lens is prepared by copolymerizing the silicon-containing monomer, the cross-linking monomer, the initiator, the ultraviolet absorber, the pigment or the dye. All the reagents in the examples can be directly purchased.
[0137] The following abbreviations are used in the examples:
[0138] TRIS: Methacryloyloxypropyl tris(trimethylsiloxy)silane
[0139] PDMS: Bis-3-(meth)acryloxypropyl polydimethylsiloxane
[0140] TMS: Trimethyl(4-vinylphenyl)silane
[0141] EGDMA: Ethylene glycol dimethacrylate
[0142] TMPTMA: Trimethylolpropane trimethacrylate
[0143] D1173: 2-Hydroxy-2-methyl-1-phenyl-1-propanone
[0144] RB19: Reactive Blue 19
[0145] Anthocyanins: Blueberry anthocyanins produced by Linbaolai Biotechnology
[0146] UV416: 2-(4-benzoyl-3-hydroxyphenoxy)ethyl acrylate
[0147] ETOH: Ethanol
[0148] The reaction components and / or diluent (anhydrous ethanol) listed in Table 1 are mixed together and stirred at room temperature for about 20 minutes until all components are dissolved to obtain a reaction preparation. The solution is purged with N2 for about 15 minutes. About 80 microliters of the above reaction preparation are transferred to a clean polypropylene concave half mold, and then covered with a matching polypropylene convex half mold. The half molds are pressed and then irradiated with light (Philips TL03, 50mW / cm 2 , 15 minutes), thereby photopolymerizing to obtain the low-water-containing soft contact lens substrates of Examples 1 to 13.
[0149] The dry contact lens substrate was immersed in a 1% mass concentration KPS aqueous solution for 20 minutes, and then immersed in a 1% mass concentration PVP aqueous solution at 80°C for 20 minutes to make PVP evenly grafted on the surface of the contact lens. Finally, the prepared contact lens was placed in 80°C purified water for hydration for 5 hours to remove the residue. The contact lens was taken out and packaged in a PP cup with a standard saline solution for wet heat sterilization for 30 minutes to obtain the final product.
[0150] Table 1: Reaction components
[0151] Example TRIS PDMS TMS EGDMA TMPTMA D1173 RB19 UV416 ETOH Anthocyanins 1 30 60 4 0.1 / 0.4 / 0.5 5 / 2 32 60 7 / 0.1 0.4 / 0.5 / / 3 37 52 10 0.5 / 0.5 / / / / 4 40 55 3.5 0.15 0.35 0.1 / / 0.9 / 5 40 58 1.5 / 0.15 0.3 0.05 / / / 6 45 48 0.1 0.05 0.5 0.3 0.05 / 6 / 7 50 43 6 0.15 0.35 0.5 / / / / 8 52 41 5 0.15 / 0.3 0.05 0.5 1 / 9 55 40 1 0.05 / 0.4 0.05 0.5 3 / 10 58 41 0.5 / 0.2 0.3 / / / / 11 60 37 0.05 / 0.5 0.4 0.05 / 2 / 12 68 20 8 / 0.5 0.5 / / 3 / 13 70 27 2.5 / 0.3 0.2 / / / / 14 42 57 0.8 0.1 / 0.1 / / / / 15 44 53 1.2 / 0.2 0.2 / 0.5 0.9 / 16 50 43 6 0.15 0.35 0.5 / / / 0.05 17 52 41 5 0.15 / 0.3 0.05 0.5 1 0.10
[0152] Note: The amount of each component in Table 1 is expressed as a percentage by mass of the total mass of each component (100%).
[0153] Comparative Examples 1 to 10 Preparation of Contact Lenses for Comparison
[0154] Referring to the preparation process of Examples 1 to 13, the reaction components and / or diluent (anhydrous ethanol) listed in Table 2 are mixed together and stirred at room temperature for about 20 minutes until all components are dissolved to obtain a reaction preparation. Use N2 to purge the solution for about 15 minutes. Pipette about 80 microliters of the above reaction preparation into a clean polypropylene concave half mold, and then cover it with a matching polypropylene convex half mold. Compress the half molds and then irradiate them with light (Philips TL03, 50mW / cm 2 , 15 minutes), thereby photopolymerizing to obtain the soft contact lens substrates of Comparative Examples 1 to 10.
[0155] The dry contact lens substrate was immersed in a 1% mass concentration KPS aqueous solution for 20 minutes, and then immersed in a 1% mass concentration PVP aqueous solution at 80°C for 20 minutes to make PVP evenly grafted on the surface of the contact lens. Finally, the prepared contact lens was placed in 80°C purified water for hydration for 5 hours to remove the residue. The contact lens was taken out and packaged in a PP cup with a standard saline solution for wet heat sterilization for 30 minutes to obtain the final product.
[0156] Table 2: Reaction components
[0157] Comparative Example TRIS PDMS TMS EGDMA TMPTMA D1173 RB19 UV416 ETOH 1 49 50 0.01 0.3 0.19 0.5 / / / 2 70 28 / / 0.5 0.5 / / 1 3 34 53 12 0.1 / 0.4 / 0.5 / 4 61 23 15 / 0.5 0.5 / / / 5 70 19 10 0.5 0.5 / / / 6 33 65 1 0.4 0.1 0.5 / / 7 26 65 8 0.5 / 0.5 / / / 8 28 60 5 0.1 / 0.4 / 0.5 6 9 75 23 1.5 0.2 0.3 / / / 10 72 26 1 0.5 0.5 / / /
[0158] Note: The amount of each component in Table 2 is expressed as a percentage by mass of the total mass of each component (100%).
[0159] Test Method
[0160] 1. Moisture content test
[0161] In the present invention, the water content of the medical device (especially contact lens) is tested according to the following method.
[0162] At room temperature, the contact lens sample prepared in the embodiment is placed in a standard phosphate buffer solution for balance overnight, the sample is taken out and blotted dry, and the mass in the hydrated state is recorded with the help of a mass balance, which is calculated as m1. The sample is then dried in an ordinary oven to constant weight, the sample is taken out and placed in a desiccator, and after cooling, it is weighed and the mass is recorded, which is calculated as m2. The moisture content of the sample is calculated according to Formula 1. For detailed methods, see GBT 11417.7-2012 Ophthalmic Optical Contact Lenses Part 7: Physical and Chemical Performance Test Methods, and the test results are listed in Table 3.
[0163]
[0164] 2. Static water contact angle test
[0165] In the present invention, the static water contact angle of the medical device (especially the contact lens) is tested according to the following method. The static water contact angle can reflect the hydrophilicity of the surface of the medical device (especially the contact lens).
[0166] At room temperature, 2 μl of standard saline solution was dropped onto the surface of the contact lens samples prepared in the examples, and the static water contact angles of these samples were tested using a static contact angle tester (model: JGW-360A). The detailed method is shown in GBT 11417.7-2012 Ophthalmic Optical Contact Lenses Part 7: Test Methods for Physical and Chemical Properties, and the test results are listed in Table 3.
[0167] 3. Oxygen permeability test
[0168] In the present invention, the oxygen permeability coefficient of the medical device (especially the contact lens) is tested according to the following method. The contact lens prepared in the embodiment is placed on the oxygen permeability tester, and the oxygen permeability tester adopts the OX-TRAN Model2 / 22H oxygen permeability tester of Mocon Company of the United States. The test temperature is set to the eye temperature (35°C) according to the standard requirements, and the test method is the coulometric method. The detailed method is shown in "GBT 11417.7-2012 Ophthalmic Optical Contact Lenses Part 7: Physical and Chemical Performance Test Methods". The test results are listed in Table 3.
[0169] 4. Elastic modulus test
[0170] In the present invention, the elastic modulus of the medical device (especially the contact lens) is tested according to the following method.
[0171] The contact lens prepared in the example was tested using the testing equipment A1-3000 desktop tensile testing machine and ET-3 electronic thickness gauge. The lens was cut into dumbbell-shaped test pieces (4 mm wide), the cut lenses were placed on the fixture and clamped, and then the tensile testing machine was started for testing. The detailed method is shown in "ASTM D882 Standard Test Method for Tensile Properties of Thin Plastic Sheeting". The measurement was performed with N=8, and the average value of the values of N=6 except the maximum and minimum values was taken as the tensile elastic modulus.
[0172] 5. Elongation at break of lens
[0173] In the present invention, the elongation at break of the medical device (especially contact lens) is tested according to the following method.
[0174] The contact lens prepared in the embodiment was tested using the testing equipment A1-3000 desktop tensile testing machine and ET-3 electronic thickness gauge. The lens was cut into dumbbell-shaped test pieces (4 mm wide), the cut lenses were placed on the fixture and clamped, and then the tensile testing machine was started for testing. The detailed method is shown in "ASTM D882 Standard Test Method for Tensile Properties of Thin Plastic Sheeting". The measurement was performed with N=8, and the average value of the values of N=6 except the maximum and minimum values was taken as the elongation at break.
[0175] 6. Lens transparency
[0176] In the present invention, the transparency of the embodiment lenses is tested according to the following method.
[0177] The contact lens prepared in the example was placed in a D65 standard light source light box with a black bottom sample tray, and the contact lens was observed with the naked eye to evaluate the transparency according to the following criteria. At the same time, another contact lens sample was taken to perform a visible light transmittance τ(λv) test using a Shimadzu UV2600i ultraviolet visible spectrophotometer, with the test band being 380nm-780nm. For detailed methods, see GBT11417.5-2012 Ophthalmic Optical Contact Lenses Part 5: Optical Performance Test Methods.
[0178] A: Excellent lens transparency; τ(λv)≥99%;
[0179] B: The transparency of the lens is slightly worse than A; 90%≤τ(λv)<99%;
[0180] C: The lens is slightly whitish and translucent; 70%≤τ(λv)<90%;
[0181] D: The lens is whitish and opaque; τ(λv)<70%.
[0182] Table 3: Lens performance test results
[0183]
[0184] The results show that the contact lenses prepared in Comparative Examples 1 to 10 are inferior to those in Examples 1 to 17 in oxygen permeability, elastic modulus, and transparency because the types or proportions of silicon monomers are not within the scope of the present invention. Specifically, the oxygen permeability of the lenses in Comparative Examples 1, 2, 5, 9, and 10 is poor, and the oxygen permeability is lower than 100×10 -11 (cm 2 / s)[mLO2 / (mL.Hgmm)]; the elastic modulus of Comparative Examples 3, 4, 6 and 7 are all poor. The lenses of the first two are hard and brittle, uncomfortable to wear and easy to break; the lenses of the latter two are too soft and inconvenient to operate and wear. The lenses of Comparative Examples 7 and 8 have poor transparency due to insufficient use of the first silicon monomer.
[0185] 7. Resistance to protein and lipid adsorption
[0186] 7.1 Anti-protein adsorption performance
[0187] The contact lenses of Example 4, Example 5, Comparative Example 4 and Comparative Example 5 were respectively placed in an aqueous solution containing FITC-labeled bovine serum albumin (0.4 mg / mL) and soaked for 24 hours. Incubate at 37°C in a constant temperature oscillating box at a speed of 100 rpm for 24 hours. Then, the supernatant was taken, the absorbance was measured, and the protein concentration and protein amount adsorbed by the sample were calculated according to the standard curve. The protein detection method was originally quoted from patent CN115028872B (Example 6: Contact lens anti-bovine serum albumin (BSA) adsorption test).
[0188] 7.2 Anti-lipid adsorption performance
[0189] The contact lenses of Example 4, Example 5, Comparative Example 4 and Comparative Example 5 were respectively placed in sample bottles containing 30 mL of triolein solution and immersed at 37° C. for 24 hours. The lenses were then carefully taken out with tweezers and the concentration of triolein in the solution was analyzed.
[0190] The triolein solution was prepared as follows: triolein was dissolved in 8 mass % KOH ethanol solution. A certain amount of triolein was weighed according to a concentration of 6 mg / mL, and 800 mL of 8% KOH ethanol solution was added to dissolve it, and then diluted to 1000 mL with 95% ethanol.
[0191] Table 5: Test results of lens resistance to protein and lipid adsorption
[0192]
[0193] The results show that the material prepared by the silicon monomer combination of the present application has unexpectedly excellent resistance to protein and lipid adsorption than the comparative example material.
[0194] 8. Anti-inflammatory properties of the materials prepared by the silicon monomer combination of the present application
[0195] 8.1 Characterization of antibacterial effect by colony count method
[0196] The contact lenses of Example 16, Example 17, Comparative Example 9 and Comparative Example 10 were respectively placed at 6 cm 2 / ml ratio into ultrapure water, and after leaching at 37℃ for 72 hours, filter the extract with a 0.2μm filter membrane for later use. Add 100μL of diluted bacterial solution (106CFU / mL) to 800μL of liquid culture medium, and then add lens extract. After incubation on a shaker for 2h, take 100μL of the reaction solution and inoculate it on the solid culture medium. After overnight reaction, take a picture of the culture medium and count it.
[0197] Preparation of liquid culture medium: weigh 5g tryptone, 5g sodium chloride, 2.5g yeast powder and place them in a 500mL conical flask, add 500mL ultrapure water, seal it with a high-temperature resistant conical flask sealing film, and place it in a high-temperature steam sterilizer at 121℃ for 20min. After sterilization, place it in a 4℃ refrigerator for standby use. Preparation of solid culture medium: weigh 5g tryptone, 5g sodium chloride, 2.5g yeast powder, 7.5g agarose and place it in a 500mL conical flask, add 500mL ultrapure water, seal it with a high-temperature resistant conical flask sealing film, and place it in a high-temperature steam sterilizer at 121℃ for 20min. After sterilization, cool it to about 60℃ and pour it into a culture dish. After the culture medium solidifies, seal it with a sealing film and place it in a 4℃ refrigerator for standby use. Activation of strains: Thaw the Escherichia coli and Staphylococcus aureus frozen at -80℃ in a clean bench, add 6mL of liquid culture medium to the bacterial solution, and place it on a shaker (200rpm, 37℃) for activation for 12h. Transfer of strains: Take the activated bacterial solution and transfer it at a ratio of bacterial solution: culture medium = 1:100.
[0198] Table 6: Test results of anti-inflammatory performance of lenses
[0199] Contact lenses Escherichia coli colony count / CFU Staphylococcus aureus colony count / CFU Example 16 5 0 Embodiment 17 3 0 Comparative Example 9 200 37 Comparative Example 10 150 29
[0200] The results show that the growth of Escherichia coli and Staphylococcus aureus co-incubated with the contact lens extracts of Example 16 and Example 17 was significantly inhibited, indicating that the contact lenses prepared by the silicon monomer combination of the present application have unexpectedly excellent anti-inflammatory properties compared with the contact lenses of the comparative examples. It can also be seen from the above comparative examples that the co-existence of the silicon polymer material of the present invention and the natural dye and / or pigment makes the silicon polymer material of the present invention have improved anti-inflammatory properties.
[0201] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A silicon polymer material, which is polymerized from silicon monomers and contains dyes and / or pigments, wherein the silicon monomers at least include a first silicon monomer, a second silicon monomer and a third silicon monomer, in, The first silicon monomer is selected from short-chain aliphatic silicon monomers, the second silicon monomer is selected from long-chain polysiloxane monomers, and the third silicon monomer is selected from aromatic silicon monomers. The weight ratio of the first silicon monomer: the second silicon monomer: the third silicon monomer is (30-70): (20-60): (0.05-10).
2. The silicon polymer material according to claim 1, wherein the first silicon monomer is selected from at least one of acrylate or acrylamide silicon monomers, such as a short-chain aliphatic silicon monomer of the following formula: R1=H or C 1-6 Alkyl, preferably H or CH3; n = 1-20, preferably 1-6, even 2-5; R2, R3 and R4 may be the same or different and are selected from one or more of H, CH3, OCH3, OCH2CH3, OSi(CH3)3, CH(OCH2CH3)2 and C(OCH2CH3)3.
3. A silicon polymer material according to any one of the preceding claims, wherein the first silicon monomer is selected from: 3-(trimethoxysilyl)propyl acrylate, 3-(trimethoxysilyl)propyl methacrylate, 3-[dimethoxy(methyl)silyl]propyl methacrylate, 3-[diethoxy(methyl)silyl]propyl methacrylate, 3-(methoxydimethylsilyl)propyl acrylate, 3-(triethoxysilyl)propyl methacrylate, 3-[tris(trimethylsiloxy)silyl]propyl methacrylate, acrylamidopropyltrimethoxysilane, (3-methacrylamidopropyl)triethoxysilane, 3-acrylamidopropyltris(trimethylsiloxy)silane, (3-methacrylamidopropyl)tris(trimethylsiloxy)silane.
4. The silicon polymer material according to any one of the preceding claims, wherein the second silicon monomer is selected from one or more of acryloxy or methacryloxy or acrylamide or methacrylamide mono- or di-terminated polydimethylsiloxanes, such as a long-chain polysiloxane monomer of the following formula: R'1=H or C 1-6 Alkyl, preferably H or CH3; p = 1-20, preferably 1-6, or even 2-5; q = 1-20, preferably 1-6, or even 2-5; m=1-100, preferably 15-60; X is O, S or NH; Y is absent or selected from: O, S, NH, NHCOO(CH2)To, NHCOO(CH2)tS or NHCOO(CH2)tNH, where t=1-20, preferably 1-10, even 2-6, especially 3-5; R'2 and R'3, the same or different, are selected from H or linear or branched, saturated or unsaturated C 1-20 Alkyl; or C 6-20 Arylalkyl, either straight chain or C 6-20 One or more of heteroarylalkyl or OCH3 or OCH2CH3 or OSi(CH3)3 or CH(OCH2CH3)2 or C(OCH2CH3)3; R'4 is H or a linear or branched, saturated or unsaturated C 1-20 Alkyl or C 6-20 Arylalkyl, either straight chain or C 6-20 Heteroarylalkyl; preferably C1-4 alkyl; W is X-(CH2)pY(CH2)q.
5. The silicon polymer material according to any one of the preceding claims, wherein the second silicon monomer is selected from the group consisting of: bis-3-(meth)acryloxypropyl polydimethylsiloxane, α-3-(meth)acryloxypropyl-w-n-butyl-polydimethylsiloxane, bis-4-(meth)acryloxybutyl-polydimethylsiloxane, α-4-(meth)acryloxybutyl-w-n-butyl-polydimethylsiloxane, bis-3-(meth)acryloxyethoxypropyl polydimethylsiloxane, α-3-(meth)acryloxyethoxypropyl-w-n-butyl-polydimethylsiloxane Siloxane, bis-4-(meth)acryloxyethoxybutyl polydimethylsiloxane, α-4-(meth)acryloxyethoxybutyl-w-n-butyl-polydimethylsiloxane, bis-3-(meth)acryloxycarbamate propyl polydimethylsiloxane, α-3-(meth)acryloxycarbamate propyl-w-n-butyl-polydimethylsiloxane, bis-4-(meth)acryloxycarbamate butyl polydimethylsiloxane, α-4-(meth)acryloxycarbamate butyl-w-n-butyl-polydimethylsiloxane.
6. The silicon polymer material according to any one of the preceding claims, wherein the third silicon monomer is selected from styryl-containing silicon monomers, such as styryl-containing silicon monomers of the following formula (E): R"1 = H or C1-6 alkyl, preferably H or CH3; R"5 and R"6, identical or different, are selected from H or linear or branched, saturated or unsaturated C 1-20 Alkyl, or one or more of Si(CH3)3; X' is absent or is selected from O or S or linear or branched, saturated or unsaturated C 1-20 Alkyl; or C 6-20 Arylalkyl, or C 6-20 heteroarylalkyl; or C 3-20 heterocyclylalkyl; R"2, R"3 and R"4, which are the same or different, are selected from one or more of CH3, OSi(CH3)3, OSiCH2CH2Si(CH3)3 and SiCH2CH2Si(CH3)3.
7. A silicon polymer material according to any one of the preceding claims, wherein the third silicon monomer is selected from the group consisting of: 4-[tris(trimethylsiloxy)silyl]styrene, 4-[tris(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[tris(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[tris(trimethylsiloxy)silyl]styrene, 4-[methoxybis(trimethylsiloxy)silyl]styrene, 4-[methoxybis(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[tris(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[tris(trimethylsiloxy)silyl]styrene, Styrene, 3-methyl-4-[dimethoxy(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[dimethoxy(trimethylsiloxy)silyl]styrene, 4-[ethoxybis(trimethylsiloxy)silyl]styrene, 4-[ethoxybis(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[ethoxybis(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[ethoxybis(trimethylsiloxy)silyl]styrene, 4-[diethoxy(trimethylsiloxy)silyl]styrene, 4-[diethoxy(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[diethoxy(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[diethoxy(trimethylsiloxy)silyl]styrene.
8. The silicone polymer material according to any of the preceding claims, comprising synthetic pigments and / or dyes or natural pigments and / or dyes, for example selected from: copper phthalocyanine, reactive blue 4, reactive blue 19, reactive blue 21, reactive blue 246, reactive blue 247, reactive yellow 15, reactive orange 78, reactive red 11, titanium dioxide, reactive black 5, D&C green 4, D&C blue 6, D&C green 6, D&C yellow 10, sodium fluorescein, brilliant blue, eosin, carmine, tartrate, amaranth, Erythrosine, new red, indigo, acid red, lycopene; in particular, the natural pigments and / or dyes contain natural pigments, for example, selected from anthocyanins, anthocyanins, wolfberry pigments, grape skin pigments, gardenia blue pigments, red rice red pigments, adzuki bean red pigments, beet red pigments; in particular, the content of the synthetic pigments and / or dyes, or natural pigments and / or dyes is 0 to 10% by mass, or 0.01 to 6%, in particular 0.2 to 4%, or even 0.5 to 2%.
9. A medical device, which is prepared from the silicon polymer material of any one of claims 1 to 13, preferably, a contact lens, a chromogenic contact lens, a colored contact lens, a corneal reshaping lens, a corneal contact lens, an intraocular lens, an artificial cornea, an intracorneal ring, an intracorneal lens, an intraocular filler, a medical device lens or a medical treatment device such as a device for treating ophthalmic diseases, preferably a soft contact lens, which may or may not be equipped with electronic devices.
10. A method for preparing a silicon polymer material according to any one of claims 1 to 13, characterized in that it comprises the following steps: -(1) mixing the required components, such as a first silicon monomer, a second silicon monomer, a third silicon monomer, a dye and / or a pigment, a crosslinking agent, and optionally an initiator or a light absorber, and optionally removing bubbles; (2) polymerizing the mixture, optionally placing it into a mold such as a contact lens mold for polymerization, preferably by thermal polymerization and / or photopolymerization; then, optionally, subjecting the obtained polymer to subsequent treatment such as molding treatment.